2015
DOI: 10.1007/s40801-015-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

How Prolific is Psychotropic Medicines Use in People with Dementia in Australia Within the Community Setting? A Retrospective Analysis

Abstract: BackgroundWhen used for a therapeutic purpose such as for psychiatric illness, psychotropic drugs may enhance quality of life; however, when used to treat behaviours associated with dementia, they may have only a modest effect but lead to negative outcomes.ObjectiveWe undertook an analysis of community-dwelling people with dementia or cognitive impairment to ascertain how prolific psychotropic medicine use is within the Australian community setting, which psychotropic medicines are being prescribed and to whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Older people receiving medication management support from home nursing services have an average age over 80 years and often have multiple health conditions . They commonly take multiple medicines (average of 10), including medications associated with increased risk of AMEs . Other common factors that predispose home nursing clients to increased risk of AMEs include recent hospital discharge, complex medication regimens, cognitive impairment and poor adherence to medicines .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Older people receiving medication management support from home nursing services have an average age over 80 years and often have multiple health conditions . They commonly take multiple medicines (average of 10), including medications associated with increased risk of AMEs . Other common factors that predispose home nursing clients to increased risk of AMEs include recent hospital discharge, complex medication regimens, cognitive impairment and poor adherence to medicines .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…9 They commonly take multiple medicines (average of 10), including medications associated with increased risk of AMEs. [9][10][11] Other common factors that predispose home nursing clients to increased risk of AMEs include recent hospital discharge, complex medication regimens, cognitive impairment and poor adherence to medicines. 12 A recent Australian study identified that 41% of home nursing clients experienced medication errors and 13% experienced AMEs requiring hospitalization or medical consultation.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…The additional burden of BPSD and pain syndromes after dementia diagnosis could trigger prescribing of psychotropics and opioids. 21 Many of these medicines have anticholinergic properties, 22 leading to higher medication burden in the year post-diagnosis of dementia. Evidence also shows that initiation of dementia medicines might be associated with prescribing cascades that lead to sequential medication prescribing for adverse drug events; for example, the initiation of anticholinergic drugs to manage urinary incontinence due to the use of cholinesterase inhibitors; 7 and this is another potential explanation for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers who are taking medication for behavioral and psychological symptoms of dementia require specific assessment to prevent stroke by careful monitoring of medication. 38 Nurses need knowledge of both medication and physical conditions to best support these clients. Sometimes family members are eager to give a higher dosage than prescribed due to anxiety about behavioral or psychological symptoms.…”
Section: Future Directions For System Reformmentioning
confidence: 99%
“…Incorporation of this advice together with information about modifiable risk factors provided by home visit nurses-for example, about diabetes, heart disease, physical activity, and smoking-will continue to expand the complexity and depth of services being provided by nurses to clients in both countries. 38 Finally, further research on the relative cost of services for people with dementia relative to other categories of health spending would help to inform future policy changes in delivery of services for this vulnerable group. How these services best complement more institutional services is an ongoing policy debate as the balance between community and residential care continues to shift and knowledge about the impact of nursing older clients with dementia in acute hospitals continues to improve.…”
Section: Future Directions For System Reformmentioning
confidence: 99%